Eficácia e segurança da toxina botulínica sobre o fenótipo clínico da rosácea e o impacto sobre a qualidade de vida e a autoestima - Takahashi, Katia Hideko (2023)
Rosacea is a chronic inflammatory skin disease, predominant in women, of multifactorial etiology, which compromises several skin structures, including proliferation and dilatation of dermal blood vessels, mainly in the central areas of the face and nearby areas, with high prevalence and affecting more than 45 million of people in the world. In Brazil, it is estimated that 10% of the population has this dermatosis. Facial lesions are accompanied by significant psychosocial impairment. So far, there is no specific treatment for rosacea. Objective: to evaluate the possible clinical benefits of the therapeutic use of botulinum toxin in patients with rosacea and to verify if there is an improvement in the quality of life and self-esteem of the participants. Methods: Thirty-three individuals diagnosed with rosacea, assisted at the Ambulatory of the Dermatology Service of the Faculdade de Ciências Médicas e da Saúde, who were assisted at Conjunto Hospitalar de Sorocaba and Hospital Santa Lucinda, and who agreed to participate in the research, were evaluated, treated, and followed up. After the diagnosis of rosacea, patients aged over 18 years were invited to participate in the study, excluding pregnant or lactating women. After signing the informed consent form, quality of life (WHOQoL-Bref and RosaQoL-BR) and selfesteem (Rosenberg) questionnaires were applied before starting treatment with botulinum toxin. The same questionnaires were reapplied at the end of the study (after 90 days). The systematization of care was, day 1, first application of botulinum toxin; day 14, application of the second dose of botulinum toxin and day 90, study final visit to record the clinical result of the treatment and the impact on quality of life and selfesteem. Results: Treatment with botulinum toxin provided clinical improvement in the dermatological condition of rosacea in 94% of the participants and a significant improvement in the quality of life scores, assessed by the two questionnaires used, and an improvement in the participants' self-esteem scores. Conclusions: The use of microdoses of botulinum toxin in patients with rosacea improves the clinical aspect of the lesions, improving quality of life and self-esteem